Only the heart can see the truth - Bayeshanov M.M (Genius Journals, 2022)
The article deals with the formation and development of the work of Antoine de SaintExupéry (1900 - 1944). He went a long way as an artist of the word, from a simple imitator to a great master. His story "The Little Prince" made his name famous all over the world. In his story, the author considers the problems of good and evil, love and hate, friendship, life, death, etc. Having become acquainted with the content of the story, the reader involuntarily thinks about the meaning of life, its problems, and their solutions
Keywords: meaning; formation; development